Neuronal Nitric Oxide Synthase Expression in the Anterior Vaginal Wall of Patients with Stress Urinary Incontinence - Ozcan, Levent; Polat, Emre Can; Onen, Efe; Otunctemur, Alper; Ozbek, Emin; Somay, Adnan; Ozbay, Nurver (Urology Journal, 2018)
Purpose: Stress urinary incontinence (SUI) and pelvic organ prolapse (POP) are common medical problems, particularly among older women. In this study, we aim to explore the relationship between the neurotransmitter nNOS in the vaginal epithelium, and the occurrence of SUI and changes of nNOS levels according to menopausal status. Matherials and Methods: Fourty women were enrolled. The patients were divided into four groups according to menstruaiton status and SUI. The vagina specimens were taken during transobturator tape application. The specimens were examined pathologically in terms of n-NOS expression. nNOS expression was compared between SUI and control groups. The results were evaluated statistically. Result: Epithelial total nNOS score in group 1 and group 3 were 2.4 ± 0.5 and 1.4 ± 0.5 respectively (P = .003). Stromal total nNOS score was found 2.2 ± 0.4 in group 1 and 1.3 ± 0.5 in group 3 (P = .001). Epithelial total nNOS score in group 2 and group 4 were 4.4 ± 0.5 and 3.5 ± 0.5 respectively (P = .003). Stromal total nNOS score was found 4.4 ± 0.5 in group 2 and 3.6 ± 0.5 in group 4 ( P = .006). Conclusion: Our results show that expression of nNOs in the anterior vaginal epithelium decreased significantly in the SUI group. Altough our findings indicate important results, well designed further studies are needed to comprehend the role of NOS pathways better in SUI pathophysiology.